(untitled) (Laisvalaikio tyrimai, 2022)
Relevance of the topic. In recent years, in the face of the COVID-19 pandemic, the traditional education system, including various non-formal education activities, has faced enormous challenges and problems. This pandemic not only claimed millions of lives, but also affected people’s daily lives and lifestyles. Most of the economic sectors in Lithuania also encountered various problems. Education, which traditionally carried out educational activities in physical environments, was not an exception and faced the sudden and strict closure of all institutions. In this situation, the application of technology and digital learning practices became the main solutions that helped to ensure the continuity of education and training, including non-formal ones (González, Bonal, 2021). Unfortunately, this decision had a particularly painful impact on organized sports for children and youth (Reece et. al., 2020). This area, of course, faced an even greater challenge than other, more theoretical, subjects, since sport, being a physical, practical and interactive activity, is not easily and simply transferred to an online environment (Iuliano et al., 2021). The problem. The idea of the problem has been increased by the fact that direct social interaction between the coach and the athlete is considered an essential condition in order to supervise the actions performed by the athletes and to ensure the high-quality implementation of the sports program (Emery & Tyreman, 2009). In the context of the pandemic, researchers began to emphasize the changed organization and execution of sports activities (Ratten, 2020; Escamilla-Fajardo et al., 2020), but there is still a lack of research-based data on the characteristics of these activities. In Lithuania, this topic has so far been little studied in the context of school sports. And although the sports activities implemented in sports schools, as state educational institutions, are regulated by the legislation of the Republic of Lithuania and the orders and instructions of the Ministry of Science, Education, Science and Sports, there is no data in the scientific literature about how informal sports education programs were implemented in them during the COVID-19 pandemic? The purpose of the study: To highlight the challenges of non-formal sports education during the Covid-19 pandemic. Research object: Challenges of informal sports education. The results. Research data revealed that the sports activities organized and carried out in sports schools during the COVID-19 pandemic had certain characteristics associated with the challenges experienced by coaches as providers of non-formal sports education programs and the challenges experienced by schoolchildren participating in sports. During the pandemic, the decrease in the motivation of young athletes to play sports, their inability to fulfill the training conditions and the negative influence of the environment in which they train on sports activities became apparent. The coaches, adapting to the changed conditions, were led to search for additional information, invest their own funds in the training process, understand the peculiarities of conducting training remotely, demonstrate their ingenuity while conducting classes, and constantly raise the motivation of athletes. However, when faced with these obstacles, they did not avoid ignoring the existing rules for the organization of sports activities. Keywords: pandemic, sport, non-formal education, coaches, athletes